Soil-transmitted helminth infections among plantation sector schoolchildren in Sri Lanka: prevalence after ten years of preventive chemotherapy. - Kithsiri Gunawardena; Balachandran Kumarendran; Roshini Ebenezer; Muditha Sanjeewa Gunasingha; Arunasalam Pathmeswaran; Nilanthi de Silva (Public Library of Science (PLoS), 2011)
BACKGROUND: The plantation sector in Sri Lanka lags behind the rest of the country in terms of living conditions and health. In 1992, a sector-wide survey of children aged 3-12 years and women of reproductive age showed >90% prevalence of soil-transmitted helminth infections. Biannual mass de-worming targeting children aged 3-18 years started in 1994 and was continued until 2005. The present study was carried out to assess the status of infection four years after cessation of mass de-worming. METHODS/FINDINGS: A school-based cross-sectional survey was carried out. Faecal samples from approximately 20 children from each of 114 schools in five districts were examined using the modified Kato-Katz technique. Data regarding the school, the child's family and household sanitation were recorded after inspection of schools and households. Multivariate analysis was carried out using logistic regression, to identify risk factors for infection. Faecal samples were obtained from 1890 children. In 4/5 districts, >20% were infected with one or more helminth species. Overall combined prevalence was 29.0%; 11.6% had infections of moderate-heavy intensity. The commonest infection was Ascaris lumbricoides, present in all five districts, as was Trichuris trichiura. Hookworm was not detected in two districts. Multivariate analysis identified low altitude and maternal under-education as risk factors for all three infections. Poor household sanitation was identified as a risk factor for A. lumbricoides and hookworm, but not T. trichiura infections. CONCLUSIONS/SIGNIFICANCE: The results indicate that regular mass de-worming of plantation sector children should be resumed along with more emphasis on better sanitation and health education. They show that even after 10 years of mass chemotherapy, prevalence can bounce back after cessation of preventive chemotherapy, if the initial force of transmission is strong and other long-term control measures are not concomitantly implemented.